Pengaruh Independence Commitment Terhadap Niat Melakukan Whistleblowing Dengan Group Cohesion Sebagai Variabel Moderasi: Sebuah Studi Eksperimen - Yulina Eka Safitri; Sany Dwita (Universitas Negeri Padang, 2019)
This study aims to empirically examine the effect of independence commitment on the intention to do whistleblowing with group cohession as a moderating variable. This type of research is classified as quasi-experimental with 2 x 2 factorial experimental design. Data in this study were collected using a questionnaire on 80 accounting students of the Faculty of Economics, State University of Padang. Data analysis was performed using One way ANOVA and MRA. The results of this study conclude that independence commitment influences whistleblowing intentions, while group cohession does not moderate the relationship between independence commitment and whistleblowing. This is evidenced by the hypothesis test, where the H1 significance value is 0.001 <0.005 and the significance value at H2 is 0.184> 0.005.